The Understanding and Readiness of Malaysian Contractors to Apply Additive Manufacturing Technology in Construction Industry - Zul Zakiyuddin Ahmad Rashid; Muhammad Zamir Ismail; Hamimah Adnan; Norazian Mohamad Yusuwan (International Journal of Supply Chain Management, 2020)
One of key technology in industrial revolution 4.0, additive manufacturing, has a potential great influence to construction industry in the future. Construction players especially contractors are expected to involve widely and directly with the technology but their understanding about the technology are unidentified. In the same time, Malaysian’s construction industry appears lack to embrace for technology that might lead the local industry be uncompetitive if it cannot engage with the new technology. The research is prepared to study the contractors understanding and readiness of additive manufacturing within the scope of a Malaysian state’s construction industry, Penang. Literature reviews have been conducted to understand about the additive manufacturing technology, its impact and future prospect in construction industry and further produced a set of survey questions, distributed to contractors and analyzed using mean score. The outcome has identified that the local contractors do not have understanding and not ready for addictive manufacturing technology. The study suggested that the authorities can learn the AM adoption rate among contractors and further formulate strategies for them to venture into the technology.